DESIGN OF HYDROKINETIC ENERGY GENERATION SYSTEM - Zengin, Namik; Aslan, Firat; Artunc, Turan Can; Aktan, Mehmet Emin; Guney, Omer Faruk (CENTRAL BOHEMIA UNIV, 2016)
Along with technological developments and increasing population, people are in need of more energy sources. This need has led researchers to go towards new energy generation methods. One of these methods is hydrokinetic energy generation, which has been studied intensively in recent years. In this study, complete design of a hydrokinetic turbine that converts kinetic energy into mechanical and electrical energy with the most efficiency using tidal water is proposed. Moreover, an undershot water wheel system is designed to gain the least dissipationless conversion of kinetic energy. The design of the hydrokinetic energy generation system is developed considering the environmental and maintenance factors, maximum efficiency and buoyancy. Calculation for the velocity of the turbine is made by using Betz's law, usually used for wind energy conversion systems. Conversion of obtained mechanical energy from the turbine to electrical energy is supplied by using a proper alternator system.
Keywords: hydrokinetic turbine; water wheel; Betz's law; energy generation; Business & Economics; Science & Technology - Other Topics; Social Sciences - Other Topics